Respostas
respondido por:
6
Tendo: (2x-y)²=1 e 3x+y=4
y=4-3x
(2x-y)(2x-y)=4x²-4xy+y² ----> Usando o método da substituição temos:
25x²-40x+16 . Usando Báskara teremos que x=4/5
y=4-3*(4/5) -------> y=8/5
x=4/5
y=8/5
y=4-3x
(2x-y)(2x-y)=4x²-4xy+y² ----> Usando o método da substituição temos:
25x²-40x+16 . Usando Báskara teremos que x=4/5
y=4-3*(4/5) -------> y=8/5
x=4/5
y=8/5
nathalya729:
Obrigada Mesmo :)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás